(3OjhGf GHf GdeYJRs - (3YHO Gddg Hf eMeO GdeYJR HGddg Hf GdeJhcd Hf GdeYJUe Hf GdQTjO GdYHGSj, GHf GdeYJR, CHh GdYHGS,J (B296 (3g` s
(3ChdgG (B:s
(3bGd eJhSdkG Edi Gddg JYGdi HGdfHj hBdg Ydjge GdUdGI hGdUdGe Edgj jGPG GdLhO hGdeLO hGdYdG hjG UGMH GdCaVGd hGdef hGdYWG s
(3BNQgG (B:s
(3jG LhgQ GdCMRGf hMjdI GdReGf, hOhdI GdeYGfj, hQhVI GdCeGfj YT dj cYeQ bhdj aHc abO caGfj s
(3fSNI KGdKI YdjgG Jedc HJGQjN (B1052(3g``s
(3hQO CjVkG JMJ Qbe (B2180(3, (B2191 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B154 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B443s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B210 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs